The first record of the subfamily Dasycerinae in Taiwan, with description of a new species (Coleoptera: Staphylinidae) - Hu, Fang-Shuo; Liang, Wei-Ren (Zootaxa, 2021)
Dasycerus poseidon Hu & Liang, sp. nov. is described and illustrated based on fresh specimens from central and southern Taiwan, which filled in the disjunct distribution between the Japanese archipelago and south-eastern Asia. The new species represents the first record of the subfamily Dasycerinae in Taiwan. The barcoding sequence of the holotype of D. poseidon Hu & Liang, sp. nov.is provided, and revealed a surprisingly large genetic distance within the genus. Detailed illustrations of D. poseidon Hu & Liang, sp. nov. by scanning electron micrograph and micro-computed tomography are also provided. Living individuals of D. poseidon Hu & Liang, sp. nov. were observed eating the mycelium of Pleurotus ostreatus in lab conditions, which represents the first direct evidence of mycophagous habits of Dasycerinae.